Pola Asuh Ibu Balita Stunting - Dita Eka Pratiwi (An-Najat, 2024)
In 2022, the number of stunting toddlers in East Semarang District Semarang City was 93 cases (3.33%) out of 2793 toddlers. The purpose of this study was to determine what factor are associated with mother parenting of stunting toddlers in East Semarang District, Semarang City. This type of research uses quantitative analytic research with a cross-sectional design. The sample of this study was 59 mothers who had stunting toddlers in Semarang City, East Semarang District using the total sampling method. Data were analyzed using chi square test. The results showed that occupation (p value 0.000), family income (p value 0.000), knowledge (p value 0.026), attitude (0.002), husband support (p value 0.000), family support (p value 0.036) and health worker support (p value 0.000) had a relationship with mother parenting of stunting toddlers. While age (p value 0.235), education level (p value 0.424), access to health services (p value 0.243) and cadre support (p value 0.176) have no relationship with mother parenting of stunting toddlers. The suggestion of this study is to increase mothers’ awareness about the importance of good parenting to prevent stunting in toddlers.